Lakuna Pemimpin Versus Kristalisasi Politik - Pabottingi, Mochtar (Pusat Penelitian Politik, 2008)
For at least the last five year of the Reform Efforts in Indonesia there has been a loud clamor concerning the serious dearth of leadership precisely at the time when it is most needed a grim fact that has indeed affected the morale of the nation Indonesia has become a leaderless country Unfortunately no one tries to unravel the serious dearth At close examination we find layers of wrong political practices that has over time undermined the normal recruitment process This paper traces the layers from the very beginning of the New Order to the present stage of the Reform Efforts including negligence in political science theories The politics of depoliticization the systemic nipping of the buds of leadership the absence of regime change in the true sense of the word the hampering of the initiative for a transitional constitution the insincerity of initiative toward truth and reconciliation commission the eruption of horizontal conflicts the practice of impunity and introduction of anachronistic politics if in reverse manner along the New Order and in the current Era of Reform Efforts all this blurs the distinction between what is right and what is wrong in politics and malignantly compromising ethical standards These were eight roots that have made leadership doomed Above all however the leadership lacuna has a great deal to do with the trampling down ofthe concernfor nation andlor nationhood especially the severity of corruption among so called people s representative and with the flagrant abuse of regional autonomy The greater the political collectivity is slighted and confused withforces ofpetty irrationalities and or primordialism the more numerous the distortions of leadership become The author maintains that only a conscious undertaking towards political crystallization could Indonesia recovers its leadership i e by the inculcation of the respectability of politics and of political profession by sharpening of the understanding of our nation s blue print and by heeding the imperative of nation in democracy by separating the business ofstate from that of religion and or primordial concern and by making room for transitional rulings in the next constitutional amendment in order to get rid of the numerous vicious circles brought about by the distortions of the transitional period as well as the anachronistic policiesIf democracy is to survive it will have to employ and use every bit ofskill and knowledge and leadership it can get hold of This complicated interdependent world in which we are living cannot be run without knowledge and skill foresight and leadership (A D Lindsay)